LGBTQ+ History in High School Classes in the United States since 1990 - Berman, Stacie Brensilver (Bloomsbury Academic, 2021)
This book is available as open access through the Bloomsbury Open programme and is available on www.bloomsburycollections.com. From grassroots campaigns and activism to top-down initiatives for and against curricular reform, this book investigates the movement to integrate LGBTQ+ history into high school history courses in the USA. Stacie Brensilver Berman charts the development of the movement from the founding of the Gay, Lesbian and Straight Education Network (GLSEN) and the passing of the Fair, Accurate, Inclusive, and Respectful (FAIR) Education Act in California, to the resurgence of conservative thought after the 2016 election. Based on 13 interviews with high school teachers about integrating LGBTQ+ history in their classes, the author reveals the challenges inherent to K-12 curricular reform amid the reluctance of a conservative nation and many of its school systems to consider an alternative vision. The book offers the first detailed portrait of a prophetic minority of educators and activists championing a more inclusive and accurate vision of American history. The book includes a Foreword written by Blanche Wiesen Cook, Distinguished Professor of History and Women's Studies at the City University of New York, USA, and Robert Cohen, Professor of Social Studies, Education, at New York University, USA.